2019
DOI: 10.1016/j.ijid.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 heterosexual transmission and association with sexually transmitted infections in the era of treatment as prevention

Abstract: Objectives: HIV-1 heterosexual transmission among individuals on antiretroviral treatment (ART) with undetectable viremia is extremely rare. The aim of this study was to evaluate the risk of sexual HIV-1 transmission and other sexually transmitted infections (STIs) in HIV-1 serodifferent couples while the index partner is on ART. Methods: HIV transmission was evaluated in 200 HIV-1 heterosexual serodifferent couples in a stable relationship (≥3 months). All HIV-positive individuals had been on ART for ≥3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…Information on all newly diagnosed HIV patients with available genotypic resistance testing in Greece were included; however, heterosexual patients were underrepresented due to their limited linkage to clinical care. This underrepresentation of heterosexuality in HIV infection has also been reported in previous studies (Knauth et al, 2020;Leal et al, 2015;Melo et al, 2019) and should be acknowledged when interpreting the results of this study in terms of the relative risk of TDR. In addition, a high percentage of individuals had an unknown route of transmission.…”
Section: Discussionsupporting
confidence: 86%
“…Information on all newly diagnosed HIV patients with available genotypic resistance testing in Greece were included; however, heterosexual patients were underrepresented due to their limited linkage to clinical care. This underrepresentation of heterosexuality in HIV infection has also been reported in previous studies (Knauth et al, 2020;Leal et al, 2015;Melo et al, 2019) and should be acknowledged when interpreting the results of this study in terms of the relative risk of TDR. In addition, a high percentage of individuals had an unknown route of transmission.…”
Section: Discussionsupporting
confidence: 86%
“…Even though they cause such trouble, some STIs, such as Chlamydia trachomatis and Neisseria gonorrhoeae , are difficult to diagnose because of the lack of symptoms in infected women. Studies have reported that there is a greater than three-fold higher risk of contracting HIV when the person already has an STI [ 86 ].…”
Section: The Fgtmentioning
confidence: 99%
“…STIs typically result in the destruction of the mucosal barriers, which leads to activation and recruitment of HIV target cells at the site of infection [ 112 ]. It has been reported that having one STI resulted in a threefold increased risk of HIV acquisition, whereas having two or more STIs increased the risk of HIV acquisition to more than sixfold [ 119 ]. In addition, women are also predisposed to HIV through asymptomatic STIs such as Chlamydia trachomatis , Neisseria gonorrhea , amongst other bacterial STIs that can sometimes be difficult to diagnose [ 120 ].…”
Section: Viral and Host Factors Modulating Hiv-1 Entrymentioning
confidence: 99%